Biomedical Journal Publishing in Yemen: Challenges and Prospects - Rashad Abdul-Ghani (University of Science and Technology, Sana’a, Yemen, 2023)
This editorial highlights some of the challenges encountered by medical journal publishing in Yemen, considering the recent launch of many medical journals by academic institutions in the context of war and humanitarian crises over the past few years. Meanwhile, it also presents prospects for enhancing the quality of medical publishing in the country.